Model Estimasi Suhu Kritis Atas pada Sapi Perah Dara Berdasarkan Manajemen Pakan - D. Suherman; B.P. Purwanto (Jurnal Sain Peternakan Indonesia, 2020)
A research was conducted in Jakarta and Bogor and during January 2014 until February 2014. The objective of research were to measure effects of critical temperature (air temperature and humidity) on indicate physiological responses for critical temperature of Fries Holland Heifer.They were fed twice daily with grass and concentrate. Six dairy heifers were used in the research. The Indicate physiological responses were heart rate and respiration frequency  for 14 days. The results show that critical temperature on physiogical responses were significantly better on cattle for ANN which for critical temperature in Jakarta and Bogor that with the same and significantly better too on cattle which respiration frequency and heart rate in Jakarta and Bogor.